Pengaruh Penerapan Sistem Manajemen Mutu Iso 9001:2008 di Perguruan Tinggi terhadap Kinerja Balanced Scorecard (Studi Kasus pada Unive - Antariksa, Walid Fajar; Setiawan, Margono; Surachman (Jurnal Aplikasi Manajemen, 2014)
The purpose of this study is to know the effect of ISO 9001:2008 implementation in Higher Education performance that is measured by Balanced Scorecard. The primary data were obtained by distributing questionnaires to the respondents who are lecturers and staffs in UB. The independent variable in this study is the implementation of ISO 9001:2008 principles while the dependent variable is the performance of the University from a financial perspective, customer perspective, internal business, and learning and growth perspective. In order to determine the effect of independent variable and dependent variable, path analysis method is used. The results of data processing show a positive influence on the application of ISO QMS university performance based on a financial perspective, customer perspective, internal business, and learning and growth perspective. From these results, the author suggests that other agencies apply the principles of ISO 9001:2008 in their organization in order to improve the performance.